Effects of Neuro-feedback Training on Balance and Ankle Instability in Patients with Anterior Talofibular Ligament Rupture - Kim, Sunho; Park, Sang woong; Yu, Wonjong (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: Anterior talofibular ligament rupture is difficult to heal, and ankle sprains can lead to chronic ankle instability; therefore, we studied the effects of neuro-feedback training on anterior talofibular ligament rupture. Methods/Statistical analysis: We selected 20 patients and divided them into two groups: a control group and a neuro-feedback group (n = 10 each). The neuro-feedback group underwent neuro-feedback training for 20 minutes while the control group meditated for 20 minutes. Both groups participated in an ankle rehabilitation program for 30 minutes, thrice a week for eight weeks. Data analysis was performed using the Statistical Package for the Social Sciences (version 21.0), and the significance level was set at 0.05. Findings: We used the numerical rating scale (NRS), foot pressure (Zebris FDM-system), one-leg standing test (OLST), timed up and go (TUG), and Cumberland ankle instability tool (CAIT) to compare the differences between the control and training groups. In both groups, the pain decreased with time. In the training group, there were significant differences in the NRS, foot pressure, OLST, TUG, CAIT, and CAIT measurements before and after the experiment. Furthermore, there were significant differences in the NRS, foot pressure, balance, and CAIT values between the groups. Improvements/Applications: Our study demonstrated the effects of neuro-feedback training in patients with ankle ligament rupture. Neuro-feedback training program is effective in reducing pain, improving balance, and improving ankle instability in patients with anterior talofibular ligament rupture.